kitābāt al-Ḥaḍar al- ma‘bad al-ṯānī ‘ašr (ma’bad al-‘ilāh Nabū): al-mawsim al-rābi’ wal-‘ašrūn 1978 - ’Abdullāh, Muḥammad Ṣubḥī
Hatran Inscriptions from the Twelfth Temple (Nabû Temple): 24th Season, 1978; ersch. 1987